2009
DOI: 10.4049/jimmunol.0802255
|View full text |Cite
|
Sign up to set email alerts
|

Drak2 Is Upstream of p70S6 Kinase: Its Implication in Cytokine-Induced Islet Apoptosis, Diabetes, and Islet Transplantation

Abstract: Drak2 is a member of the death-associated protein family and a serine threonine kinase. In this study, we investigated its role in β cell survival and diabetes. Drak2 mRNA and protein were rapidly induced in islet β cells after stimulation by inflammatory lymphokines known to be present in type 1 diabetes. Drak2 up-regulation was accompanied by increased β cell apoptosis. β cell apoptosis caused by the said stimuli was inhibited by Drak2 knockdown using small interfering RNA. Conversely, transgenic Drak2 overe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 23 publications
0
30
0
Order By: Relevance
“…While the role of Drak2 in the EAE model was intrinsic to the T cells, and due to increased susceptibility to apoptosis of autoreactive cells, other data suggest that Drak2 may contribute to T1D by affecting survival of pancreatic β cells [14]. Treatment of islet cells with inflammatory cytokines led to the upregulation of Drak2 expression in these cells, which correlated with islet apoptosis.…”
Section: However Drak2mentioning
confidence: 99%
See 4 more Smart Citations
“…While the role of Drak2 in the EAE model was intrinsic to the T cells, and due to increased susceptibility to apoptosis of autoreactive cells, other data suggest that Drak2 may contribute to T1D by affecting survival of pancreatic β cells [14]. Treatment of islet cells with inflammatory cytokines led to the upregulation of Drak2 expression in these cells, which correlated with islet apoptosis.…”
Section: However Drak2mentioning
confidence: 99%
“…Although many lines of evidence indicate that Drak2 plays a critical role within the T cells, other data suggested that Drak2 expression in β-islet cells augments T1D [14,23]. Therefore, we investigated whether Drak2 expression in T cells, β-islet cells, or both cell types regulated disease in the NOD model of T1D.…”
Section: Organization Of the Dissertationmentioning
confidence: 99%
See 3 more Smart Citations